연어(Oncorhynchus keta)의 초기 생활사에 아질산성 질소 노출이 미치는 급성 독성 - 이유진; 고지예; 조규석; Yu Jin Lee; Ji Ye Go; Kyu Seok Cho (한국해양생명과학회지, 2024)
This study examined the acute toxicity of nitrite nitrogen(NO2--N) on the early life stages of chum salmon(Oncorhynchus keta). The results showed that LC50 values for nitrite nitrogen decreased progressively as the fish developed through their early life stages. In the alevin stage, the 96-hour LC50 value was measured at 89.98 mg/L, while in the fry stage, it was 29.36 mg/L, and in the parr stage, it was 1.89 mg/L, indicating that the toxicity of nitrite nitrogen increased as the developmental stage progressed. At 24 hours, alevin had a 10% mortality rate at 160 mg/L and 56.7% at 240 mg/L of nitrite nitrogen. By 72 hours, mortality rose to 90% at 160 mg/L, with 100% mortality at levels above 200 mg/L. At 96 hours, mortality reached 16.7% at 40 mg/L and 96.7% at 160 mg/L. For fry, at 24 hours, mortality was 3.3% at 30 mg/L, 56.7% at 50 mg/L, and 83.3% at 60 mg/L, with 100% mortality at 50 mg/L after 96 hours. In the parr stage, the mortality rate was 10% at 1.6 mg/L after 24 hours, with all individuals dying at 6.4 mg/L. After 48 hours, mortality increased to 56.7% at 3.2 mg/L, and at 96 hours, mortality reached 83.3% at 3.2 mg/L and 100% at 6.4 mg/L. Therefore, the alevin stage showed lower sensitivity to nitrite due to reduced nitrite absorption, but as the fish progressed to the fry and parr stages, gill development led to increased nitrite toxicity, with the parr stage showing the highest sensitivity. 연어(Oncorhynchus keta)의 초기 생활사 단계에서 아질산성 질소(NO2--N)에 대한 LC50 값은 시간이 지남에 따라 감소하는 경향을 보였다. Alevin 단계의 96시간 LC50 값은 89.98 mg/L이었고, fry 단계에서는 29.36 mg/L, parr 단계에서는 1.89 mg/L로 측정되어 성장 단계가 진행될수록 아질산성 질소의 독성은 증가하였다. Alevin 단계의 폐사율은 24시간째 아질산성 질소 160 mg/L에서 10%, 240 mg/L에서 56.7%로 나타났고, 72시간째 160 mg/L에서는 90%, 200 mg/L 이상에서는 100%를 기록하였다. 96시간째는 40 mg/L에서 16.7%, 160 mg/L에서는 96.7%의 폐사율이 관찰되었다. Fry 단계의 폐사율은 24시간째 아질산성 질소 30 mg/L에서 3.3%, 50 mg/L에서 56.7%, 60 mg/L에서 83.3%이었으며, 96시간째는 50 mg/L에서 모든 개체가 폐사하였다. Parr 단계의 폐사율은 24시간째 아질산성 질소 1.6 mg/L에서 10%, 6.4 mg/L에서 100%이었고, 48시간째 3.2 mg/L에서 56.7%, 96시간째 3.2 mg/L에서 83.3%, 6.4 mg/L에서는 100%를 보였다. 따라서 alevin 단계는 아질산성 질소의 체내 흡수가 적어 독성 민감성이 낮았으나, fry와 parr 단계로 진행되면서 아가미 발달과 함께 독성이 증가하였으며, 특히 parr 단계에서는 가장 높은 민감성을 보였다.